A new approach towards int-soft hyperideals in ordered ternary semihypergroups. (4th July 2022) - Talee, Aakif Fairooze; Abbasi, Mohammad Y.; Hila, Kostaq; Khan, Sabahat Ali
Abstract: This paper deals with a class of algebraic hyperstructures called ordered ternary semihypergroups which are studied in terms of int-soft hyperideals. We introduce the notion of int-soft hyperideals in ordered ternary semihypergroups and investigate some properties of them. We also introduce the concepts of convex soft sets and int-soft points and discuss their properties. Moreover, the classes of regular and intra-regular ordered ternary semihpergroups are characterized in terms of int-soft hyperideals.